2014
DOI: 10.1521/pedi_2013_27_126
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Subgroups of Adolescents Diagnosed With Borderline Personality Disorder: A Latent Class Analysis of Personality Features

Abstract: Research suggests that borderline personality disorder (BPD) can be diagnosed in adolescents and is marked by considerable heterogeneity. This study aimed to identify personality features characterizing adolescents with BPD and possible meaningful patterns of heterogeneity that could lead to personality subgroups. The authors analyzed data on 60 adolescents, ages 15 to 18 years, who met DSM criteria for a BPD diagnosis. The authors used latent class analysis (LCA) to identify subgroups based on the personality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…First, in a previous study (Ramos et al, 2014) using a latent class analysis, it was possible to observe that adolescent BPD could be understood within an internalizing/externalizing framework, which we intend to confirm in the current study using a structural equation model. Second, we will evaluate the association among personality traits, internalizing and externalizing dimensions, and attachment perception.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…First, in a previous study (Ramos et al, 2014) using a latent class analysis, it was possible to observe that adolescent BPD could be understood within an internalizing/externalizing framework, which we intend to confirm in the current study using a structural equation model. Second, we will evaluate the association among personality traits, internalizing and externalizing dimensions, and attachment perception.…”
mentioning
confidence: 55%
“…Considering the importance of simultaneously evaluating the symptomatic criteria and the underlying personality traits of adolescents with BPD, in a previous contribution we also established a connection of adolescent BPD with the internalizing/ externalizing model (Ramos, Canta, de Castro, & Leal, 2014). Through the use of a latent class analysis, we found two distinct adolescent BPD profiles, with significant differences at the level of personality traits, conceptualized in terms of internalizing and externalizing personality dimensions.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Given the importance of accurate identification of BPD, and recognizing the challenges of making this diagnosis in the midst of high comorbidity and self-injury in clinical samples, this study evaluated the presence of distinct profiles of BPD symptoms in 75 teenaged girls ( A similar approach has recently been applied to adolescents with BPD (Ramos, Canta, de Castro, & Leal, 2014). This study used LCA to identify subgroups within the sample based on personality traits.…”
Section: The Current Studymentioning
confidence: 99%
“…Another study employing a latent class analysis on sixty adolescents diagnosed with BPD identified subgroups based on personality traits (Ramos, Canta, de Castro, & Leal, 2014). Across the sample, the BPD symptoms with the highest prevalence were impulsivity (96.7%), affect instability (98.3%) and anger (73.3%).…”
Section: Latent Class Analysismentioning
confidence: 99%